Protective and decorative coatings : paints, varnishes, lacquers, and inks : raw materials for varnishes and vehicles - Mattiello, Joseph J. (Wiley)
Contiene: The paint and varnish industry; Drying oils; Resins; Driers; Thinners, solvents; Natural minerals; Ethers.